Familial discoid lupus erythematosus. - Ferrara, M. (European Journal of Pediatric Dermatology, 2020)
Less than 3% of DLE cases begin before the age of 10 (2) and, as in adults, DLE prevails in females in the ratio of 2:1. The clinical features are extremely variable: first of all we talk about a localized form when the lesions are essentially localized to the head and about a disseminated form when other sites are involved. Both can be associated with hyperkeratosis and atrophy in the classic form. However, these characteristics may be missing: in this case the inflammatory infiltrate can affect only the dermis (DLE in plaques) or even the subcutaneous (lupus panniculitis or lupus erythematosus profundus). From a clinical point of view, there may or may not be photosensitivity in forms that do not affect the face; in cases without photosensitivity an aggravation factor can be the cold as in our case. Laboratory tests are usually within the normal range in DLE. However, in some cases autoantibodies can be found, usually only ANA. […]